Paths in and Out of Academia in Russia: Implementation of Situational Approach - Anna SVIRINA; Maksim SOLODUKHO; Natan SOLODUKHO (Communications of International Proceedings, 2020)
The paper analyzes the reasoning behind entering and exiting academia in case of Russian universities. It investigates the issue of coming in and out of academia in case of constant changes that occurred in the academic world in the past 25 years. They have led to drastic changes in the academic world and greatly influenced the paths one had to and out of academia. In this paper, we try to see whether the motivation to become an academician or leave this world is different for the Russian setting compared to what exists in the Western academic world.
Keywords: Academia; Career; Situational Approach.